Whatsapp : The Dispute between Social Media Using and Hoax Spreading - isma adila; Widya Pujarama; Arif Budi Prasetya; Ika Rizki Yustisia (Brawijaya Journal of Social Science, 2020)
Realizing good governance in communication activities through the media in Indonesia is not easy. Social media besides providing convenience also bring negative impacts for its users. Disinformation or hoax messages are disseminated via Whatsapp cause panic and anxiety. The older adult or the so-called silver surfer group is claimed to be a vulnerable group that consumes and/or disseminates hoax messages because their consumption patterns of media products are often carried out in the form of reinforcing their personal opinions, not cross-check information received. This study uses qualitative research methods with the aim to provide an overview of phenomenon about the spread of hoax messages by the older adult in their Whatsapp group and the social consequences. The lack of understanding media literacy impacts the difficulty of differentiating factual information and hoaxes. This research provides education to the public about the importance of media literacy, especially in the dissemination of disinformation, as well as giving an overview about the importance of media literacy, especially in the scope of the smallest organization, families. This also can be an academic consideration for the risk mitigation activities of the spread of hoax messages that were practiced by the Ministry of Information and Communication (Kominfo RI).